BENTUK PENYAJIAN TARI RADDAT YA MUHAMMAD DI DUSUN SEBADI KECAMATAN TELUK KERAMAT KABUPATEN SAMBAS - Kalba, Milda Putri; Ismunandar, Ismunandar; Muniir, Asfar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstrac     The research was aimed to find the form of presentation of Raddat Ya Muhammad dance in Sebadi, Teluk Keramat, Sambas regency. The form of presentation of this dance displayed on the Mawlid of the Prophet in 1960’s, later in 2014 dance Raddat ya Muhammad was presented in Jakarta as the introduction of dance. The method was descriptive method with qualitative research and using choreography approach.  The sources of the data were Syahril, alm Abdul Hadi, A Muin Ikhram. The data were in the form of interviews, observation and documentation. The data were collected by observation, interview, and documentation. The technique of data validity was in the form of observation lengthening and triangulation. The technique of data analysis was using interactive data analysis, divided into three stages, analysis during the field, data reduction and data presentation. The result of this research was consisting of various early tahto steps, Almustofa steps, group choreography consisting of unison design, straight design, and alternate cell design. The accompanying music were tahar, kedumbak, rumba, the theme in dance Raddat Ya Muhammad tells folklore, makeup used beautiful makeup, fashion clothing used baju kurung, pants brackets, earrings, rocking shoots, lotus, and place of performances featuring a work of dance that is often called the stage, the layout that serves only as a light only. The results of this research can be used as reference materials for teachers or educators and make it as a reference in the learning of cultural arts and school skills (especially dance lessons).                                                                                                                                                                                                          Key words : Persentation Form, Raddat Dance Ya Muhammad